Health Care Access by Weight Status in the State of Georgia - Elizabeth Pullekines; Janani Rajbhandari-Thapa (Georgia Southern University, 2019)
Background: Obesity continues to grow in prevalence in the United States and within the state of Georgia. Obesity is a risk factor for many chronic and preventable diseases. As such, obese individuals have higher demand for health care services than non-obese individuals. In addition, the health care system can play a role in preventing obesity and other conditions caused by obesity. Methods: This research follows the established positive relationship between health care use and access to health care services through insurance coverage. The paper analyzes how the Affordable Care Act (ACA) affected insurance coverage and access to health care services for obese and overweight individuals. A logistic regression was used on data from the Behavioral Risk Factor Surveillance System. Results: Results concluded that Georgia residents were less likely to have health insurance after the ACA was passed. Significant association between weight status and health care services through insurance coverage was not found. The results show that increased access to care including preventive services for obese and overweight post ACA is yet to be observed. Conclusions: Findings present a need for lawmakers to develop policy to promote insurance enrollment for Georgian residents. This is critical as the state sees an increase in overweight and obesity that are risk factor to many chronic disease conditions. Keywords: Affordable Care Act, obesity, Iisurance, healthcare